If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + -37 = x Combine like terms: -8 + -37 = -45 -45 = x Solving -45 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -45 + -1x = x + -1x Combine like terms: x + -1x = 0 -45 + -1x = 0 Add '45' to each side of the equation. -45 + 45 + -1x = 0 + 45 Combine like terms: -45 + 45 = 0 0 + -1x = 0 + 45 -1x = 0 + 45 Combine like terms: 0 + 45 = 45 -1x = 45 Divide each side by '-1'. x = -45 Simplifying x = -45
| -32+11x=73+4x | | 4x+205=14x-5 | | 3x+2(x+4)=-23 | | xsquared-14x+14=4-8x | | 2t+4t-2=26 | | 24x^2=18x | | x-1=-(1+x) | | 999+k=1721 | | -48+9x=60+5x | | -9=b/2 | | 68-2x=25x+17 | | 8w-28=6(w-24) | | 2x^2+5x-16=0 | | -9=2a+a | | 8w-28=6w-24 | | -43+7x=17+4x | | 1=6-y | | 26x-5-13x+4=24x-6-11x+15 | | -2[x-3]=-12 | | 5x+3=40 | | 8-(4x+m)=5(x+6)-2The | | -75+6x=-x+30 | | 8(1+5r)-7r=35+6 | | 0.25y-3+4=12 | | 7=16x | | -57-4x=33-9x | | -10=x+x | | 47=17-n | | 2s-5s=63 | | 6n+2=2(n-17) | | 13=a-8 | | 9x^3-52x^2-12x=0 |